Magnetic Resonance Imaging Delineates the Ischemic Area-at-Risk and Myocardial Salvage in Patients with Acute Myocardial Infarction - Berry, Colin (2010)
BACKGROUND: The area-at-risk (AAR) is a key determinant of myocardial infarction (MI) size. We investigated whether MRI measurement of AAR would correlate with an angiographic AAR risk score in patients with acute MI. METHODS AND RESULTS: Bright blood T2-prepared steady-state free-precession MRI (T2-SSFP MRI) was used to depict the AAR in 50 consecutive acute MI patients while infarct size was measured on gadolinium late contrast enhancement images. AAR was also estimated using the APPROACH and DUKE angiographic jeopardy scores and ST elevation score. Myocardial salvage was AAR minus infarct size. Results are mean±SD unless specified. Patients were of 61±12 years of age; 76% had ST elevation MI; 20% had prior MI. All underwent MRI 4±2 days following initial presentation. The relationship between MRI and the APPROACH angiographic estimates of AAR were similar (overall size relative to LV mass (32±12% vs. 30±12% respectively, p=0.33)), correlated well (r=0.78; p<0.0001) and had 2.5% bias in Bland Altman analysis. The DUKE Jeopardy Score underestimated AAR relative to infarct size and correlated less well with MRI (r=0.39; p=0.0055). ST elevation score underestimated infarct size in 19(50%) subjects and did not correlate with MRI (r=0.27; p=0.06). Myocardial salvage varied according to TIMI flow grade at the end of angiography/PCI (p=0.04) and TIMI flow grade was a univariable predictor of myocardial salvage (p=0.011). In multivariable analyses, infarct size was predicted by T2-SSFP MRI (p<0.0001). CONCLUSIONS: T2-SSFP MRI delineates the AAR and enables estimation of myocardial salvage when coupled with a measurement of infarct size.